Numerical simulation of bileaflet heart valve prostheses in aortic position / Kamalasrinny Radhakrisnnan - Kamalasrinny , Radhakrisnnan (2012)
Modeling and simulation of heart valves had been a demanding biomechanical problem due to the variation in anatomy of heart valves, 3D anisotropic material behavior and the pulsatile physiological behavior. The application of Fluid Structure Interaction (FSI) models had become a key tool in optimizing the current existing designs of mechanical heart valves which eventually offers constructive and valuable information to the cardiologists. As such, a FSI numerical simulation was carried out to analyze the dynamic behaviors of the leaflets during its opening and closing stage with the presence of pulsatile aortic velocity blood flow and the local phenomena experienced by the blood flow throughout the simulation. Coupling was performed to reach this objective using a commercial computational fluid dynamics package in ANSYS. The prosthetic mitral valve was modeled together with the inlet and outlet of the aortic tract to simulate its actual position in the heart. The pressure and velocity distribution in 1 cardiac cycle were obtained at specified time to differentiate their distributions during systole, peak systole, diastole and peak diastole region. The results obtained were compared with the existing results from related journals. Future work on performing simulation that are closer to the aortic root geometry, and parameters that need to be taken into consideration in future research had been discussed as well to discover the flaws present in the current design and the steps that can be taken to improve them.